Od „Widsith” do „Pieśni o Wiklefie” – przykłady średniowiecznych zabytków kultury łączących Polskę i Anglię - Laskowski, Maciej (Scripta Neophilologica Posnaniensia, 2022)
The article expands on selected medieval monuments of culture that are common for Poland and England. Particularly, the paper portrays Polish-English cultural, historical and literary relations, which may not be very obvious at first sight, but which have solid foundations and some of which date back to the times before the formal creation of both of these countries. The timeframe focuses on the Middle Ages mainly, as the cultural monuments under study – potent in the past – are or seem forgotten by the present-day reading public. Consequently, it is hoped that the subsequent text will constitute a recommendation of these cultural monuments, which once found their place in the history of Poland and England.